DIRECTIONS FOR FORMATION OF LOCAL BUDGETS - Shoydaliyev Umid Eshquvat o'g'li (Web of Journals Publishing, 2023)
The current state of reforming the budget system and rational and effective use of state budget funds in the Republic of Uzbekistan makes it difficult for economists to find solutions to a number of new problems. In fact, at the current stage of the development of the budget system in the Republic of Uzbekistan, the current public finance system does not meet modern requirements and does not allow for an objective and reliable assessment of budget expenditures related to the ongoing budget policy, state programs adopted in the medium term, and the introduction of internationally recognized methods of budget planning. Problems such as slowness are evident today.